Shape dependence of the electrochemical properties of α-Fe2O3 particles as anode materials for lithium ion batteries. Issue 32 (14th March 2016) - Lu, J. F.; Tsai, Y. Y.; Tsai, C. J.
Abstract : Cyclic performance and coulombic efficiency at 0.1C for electrodes fabricated using different shapes of α-Fe2 O3 nanoparticles. Abstract : Hematite (α-Fe2 O3 ) nanoparticles with different shapes were prepared by hydrothermal treatment of ferric solution at 180 °C with the addition of different amounts of water to the EDA ratio in the reaction systems. The particle shapes obtained from the reaction systems include irregular polyhedra, hexagonal bipyramids, elongated bipyramids, and rhombohedra as the amount of EDA in the reaction systems increased. The electrochemical measurements of these different particle shapes as materials for lithium ion batteries showed that the best performance both in specific capacity and rate capacity were observed to be the shape of hexagonal bipyramid. The results showed that, beside the size of the particles, the shape of the particles being confined by specific surfaces is another important factor that dictates the electrochemical performance of α-Fe2 O3 .